Public Participation Reconstruction in Legislation Formation in Indonesia Post-Pandemic - Mohamad Roky Huzaeni, Rocky Huzaen; Nada, Izzah Qotrun (The Sunan Ampel Review of Political and Social Sciences, 2022)
Covid-19 is not only a dangerous disease for humans, this pandemic also has an impact on the sustainability of democracy in Indonesia. In the last decade, Indonesia's democracy index has declined and even reached its lowest position in 2020. This is due to the lack of freedom and public involvement in actualizing their political interests, including in the formation of laws and regulations. The principle of openness in the formation of laws and regulations is intended to prevent corruption in legislation. But in fact, the implementation of public participation in the formation of laws and regulations is only a pseudo ritual. This research method uses normative research with approaches (statue approach, case approach and comparative approach). The results of this discussion find that the decline in Indonesia's democracy index is the lack of community involvement caused by the lack of government transparency in operating and less proactive legislators in preparing and screening of public participation and also it's still doesn't exist the absence of regulations governing participation mechanisms that accommodate input from the community. Then there is a need for improvements to the parliamentary system by reconstructing public participation which is not only limited to parliamentary agreements but also provides opportunities for the public to take part and have the right to an opinion and the right to ask for answers to opinions.